Blackleg in cattle in Kazakhstan: regional epizootology, seasonal patterns, and molecular identification of the pathogen - Mussoyev, Assilbek; Abutalip, Aspen; Nurpeisova, Ainur; Suchshikh, Vladislava; Makulbekov, Yerkebulan; Yoo, Han Sang; Adambayeva, Akmaral; Kalkabayev, Kanat; Rametov, Nurkuisa; Kassenov, Marhabat; Abay, Zhandos (Frontiers in Veterinary Science, 2025)
IntroductionBlackleg (emphysematous carbuncle) is a highly lethal infection of cattle and remains a significant veterinary concern in Kazakhstan. Understanding epidemiological patterns and characterizing the causative agent are crucial for improving surveillance and prevention strategies.MethodsWe analyzed blackleg outbreaks in Kazakhstan from 2015 to 2024 and conducted laboratory investigations on suspected cases in 2023. Isolation and identification of the pathogen were carried out using cultural, morphological, and molecular methods, and phylogenetic analysis was performed based on the 23S rRNA gene fragment.ResultsDuring 2015–2024, 12–81 outbreaks were reported annually, with an average of 24.6 ± 8.9 outbreaks per year (range 12–81) and 1–3 affected animals per outbreak. A pronounced seasonal peak occurred in November (32.2%). Regional differences were significant: the highest proportion of outbreaks was in West Kazakhstan (55.5%), while low rates were recorded in North Kazakhstan (0.7%) and Akmola (2.1%). Clinical and pathological changes corresponded to classical signs of blackleg. Clostridium chauvoei was isolated and identified from two cases in West Kazakhstan and Abai regions. Cultural, morphological, and biological studies confirmed the diagnosis, and phylogenetic analysis verified species identity and provided new genetic data for regional strains.ConclusionThese findings enhance the understanding of blackleg epizootiology in Kazakhstan and contribute to the establishment of a regional genetic database of Clostridium chauvoei, supporting improved surveillance, as well as the development of diagnostic and preventive strategies.